Comparison of Measurement of Intraocular Pressure between Goldmann Applanation Tonometer and Non-Contact Air Puff Tonometer - Liaquat Ali Shah, Attaullah Shah Bukhari, Muhammad Ali Shar, Shahid Jamal Siddiqui (Pakistan Journal of Ophthalmology, 2018)
Objective: To compare measurement of intraocular pressure between Goldmann Applanation Tonometer and Non-Contact Air Puff Tonometer. Study Design: Clinical Observational Study. Place and Duration of Study: This study was carried out at Out Patient Department of Ophthalmology, Khairpur Medical College Hospital, Khairpur Mir?s from January 2017 to March 2017. Methodology: In this Clinical Observational Study, intra ocular pressures of 400 eyes of 200 patients, Male 125 (250 eyes) and Female 75 (150 eyes) with age ranging from 20 to 70 years, were measured by Goldmann Applanation Tonometer (GAT) and Non-Contact Air Puff Tonometer (APT), results and differences were noted. Results: The mean IOP was 16mmHg (SD = 6 mmHg) measured by APT and 13mmHg (SD = 3 mmHg) measured by GAT. The calculated difference between APT and GAT was 3 ? 2.5 mmHg. Pressure taken by APT was slight high (i.e. around 3 mmHg). Conclusion: Air Puff tonometry gives slightly higher results (about 3mmHg) but is safe and easy than Goldmann Applanation tonometer. There is no fear of spread of infection and can be used easily in mass screening programs. Key Words: Goldmann Applanation Tonometer, Air-Puff non-contact Tonometer, Intraocular pressure, Glaucoma.